Didactic Reform: Organising Learning Projects on Distance and Applications in Taxicab Geometry for Students Specialising in Mathematics - Cam Tho, Chu; Phuong, Tran Thi Ha (VNU Journal of Science: Education Research, 2017)
In the early 20 th century, Hermann Minkowski (1864-1909) proposed an idea about a new metric, one of many metrics of non-Euclidean geometry that he developed called Taxicab geometry. The purpose of this paper is to design activities so that students can construct the concept of distance and realise practical applications of Taxicab geometry.